How many hours do people sleep in Bangladesh? a country-representative survey - Md. Yunus, Fakir; Khan, Safayet; Akter, Tahera; Rahman, Mahfuzar; Reja, Saifur; Islam, Akramul; Jhohura, Fatema (© 2016 Blackwell Publishing Ltd., 2016)
This article was published in Journal of Sleep Research [© 2016 Blackwell Publishing Ltd.] and the definite version is available at: http://onlinelibrary.wiley.com/doi/10.1111/jsr.12381/full